FAMILY CURTONOTIDAE - Mello, Ramon Luciano (Zootaxa, 2016)
The family Curtonotidae is represented in the New World only by the genus Curtonotum Macquart. This catalogue presents the three species of Curtonotum recorded from Colombia: C. bivittatum Klymko & Marshall, C. trypetipenne Hendel and C. tumidum (Enderlein).